Os serviços Internet Banking e a sua utilidade no relacionamento entre cliente e Instituição Financeira - Ferreira, Fernanda Alves (2021)
Observing the importance of financial institutions for the economy, this work verified how useful the use of internet banking is being for micro-enterprises in a specific bank branch located in the municipality of Guarapuava-Paraná. For a better analysis, Institutional theory was used as a basis, with support from the stages of habituation, objectification and sedimentation defined by Tolbert and Zucker (1999). As for the methodology, the quantitative research was used in the first phase, which was collected through questionnaires sent to companies that use internet banking. 78 questionnaires were answered and validated, with 15 multiple-choice questions and 3 descriptive questions. In the second phase there was an interview with one of the bank managers who is responsible for the legal entity, where the interview was based on the answers to the questionnaire applied to internet banking users. Most internet banking users consider the tool as an innovation and emphasize that this tool helps in their needs, and they feel satisfied and secure, and that they intend to continue using the tool and recommend its use to others. Users such as the employee claim that the tool facilitates and streamlines the process within the branch, thus facilitating the users' daily lives, thus creating a consensus regarding the use of internet banking. With this we observe that internet banking brings benefits to users as well as to the financial institution, assuming that its use will become increasingly sought after. In the first phase of regularization, the institution needed to include a tool that people could use in a practical, fast and safe way, without the need to travel to a branch characterized by the innovation process that took place in the banking sector. In the objectification phase, users had to adapt to the use of internet banking, considering that the city of Guarapuava is very conservative, and this culture influences people to have some difficulties in using the platform. And finally, the sedimentation phase that occurs in maintaining the use of internet banking and for this to happen, the bank always seeks to be aware of the needs of users so that the platform is always able to meet their needs. As a contribution, this study covered how the institutionalization process took place within the banking sector for legal entities that use the internet banking platform and identified the supports and improvements that can be seen.